2018
DOI: 10.3389/fonc.2018.00499
|View full text |Cite
|
Sign up to set email alerts
|

Management of Intracranial Metastatic Disease With Laser Interstitial Thermal Therapy

Abstract: Treatment approaches for metastatic brain tumors continue to evolve, with increasing recent emphasis on focal therapies whenever possible. MRI-guided Laser Interstitial Thermal Therapy (LITT) is a minimally invasive surgical option that has broadened the capability of the neurosurgeon in treating difficult-to-treat intracranial lesions. This technology uses image-guided delivery of laser to the target lesion to generate heat and thereby ablate pathological tissue and has expanded the neurosurgical armamentariu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 22 publications
(24 reference statements)
0
26
0
Order By: Relevance
“…Salehi et al [40] in a study with 25 patients with BM treated with LITT established a cutoff volume of 5.62 cm 3 where patients with equal or smaller lesions had longer PFS. On a univariate analysis, the authors also reported that patients with coverage equal to 97% or lower had a significantly shorter PFS when compared to patients with greater than 97% of lesion coverage.…”
Section: The Use Of Litt To Treat Brain Metastasesmentioning
confidence: 99%
“…Salehi et al [40] in a study with 25 patients with BM treated with LITT established a cutoff volume of 5.62 cm 3 where patients with equal or smaller lesions had longer PFS. On a univariate analysis, the authors also reported that patients with coverage equal to 97% or lower had a significantly shorter PFS when compared to patients with greater than 97% of lesion coverage.…”
Section: The Use Of Litt To Treat Brain Metastasesmentioning
confidence: 99%
“…There are two different systems on the market, both of which provide visual representations of temperature over a certain time to induce cell death, usually 43°C for 10 min. 8 …”
Section: Principles Of Littmentioning
confidence: 99%
“… 3 Ideally the complete lesion would be covered by the thermal damage threshold (TDT) lines, although the presence of eloquent areas or heat sinks such as ventricles and blood vessels can limit lesion coverage. 8 The size of the lesion also limits ablation. Four cases of malignant cerebral edema requiring hemicraniectomy have been described after LITT, with the volumes ranging from 29 to 70 cm 3 .…”
Section: Principles Of Littmentioning
confidence: 99%
See 1 more Smart Citation
“…Laser interstitial thermal therapy (LITT) has become a frequently used treatment for CNS lesions in the past decade, with recent evidence suggesting that LITT may create local disruption of the BBB and BTB [10]. LITT is a stereotactic, minimally invasive, cytoreductive technique that can be used to create targeted and conformal thermal injury to treat a wide array of CNS lesions [11][12][13]. The technique was first described in 1983 but only recently gained traction, primarily due to technological advances, such as MRI thermometry and improved laser probe design [14,15].…”
Section: Introductionmentioning
confidence: 99%